(untitled) (Research, Society and Development, 2022)
Objective: To identify the changes that occurred in older people during social distancing in the COVID-19 pandemic. Methodology: Quantitative, descriptive study, carried out from August 2020 to March 2021 with elderly people participating in an extension project at a public university in the Northeast. Data were collected through an electronic form sent through a messaging application (WhatsApp), analyzed by descriptive statistics and expressed in absolute and relative frequencies. Results: 91.7% of the elderly said that there was a change in mood, making them sadder during social distancing; 80% started to use cell phones more to communicate; 80% said they performed physical activity at home and 60% added a new activity to their daily routine. Conclusion: The changes found occurred in the social, mental and physical spheres. However, among these changes, the adoption of new habits seems to have been adopted as a way of adapting to the scenario of social isolation imposed by the pandemic, being very favorable for all those surveyed.